Curbing Corruption Through Media Role in Iraq - Falih Hussein, Maytham; Jano, Zanariah; Hashim, Rahman (Opción, 2019)
Media play an important role in combating corruption and promoting good governance. Bribery is being carried out with fear that their acts may be dis- covered and cultivated from various successful bribery. Perpetrators betray their own integrity to commit bribery. Corruption has risen in the governance of Iraq. Media have the possible to form awareness by keeping the corrup- tion report immense on the public agenda. The main purpose of this study was to discuss factors in curbing corruption through media in Iraq. The ma- jor research question was whether the media role has assisted in preventing corruption in Iraq. The intention of this study is to yield factors in curbing corruption through media in Iraq. Present methodologies were quantitative methods that utilize a survey approach. The present study obtained 320 re- spondents from Iraq. The study main outcomes focus on developing the con- ceptual framework of factors in curbing corruption through media in Iraq.